2021
DOI: 10.3390/e23091172
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Crude Oil Futures Market and Chinese/US Stock Index Futures Market Based on Breakpoint Test

Abstract: Combined with the B-P (breakpoint) test and VAR–DCC–GARCH model, the relationship between WTI crude oil futures and S&P 500 index futures or CSI 300 index futures was investigated and compared. The results show that breakpoints exist in the relationship in the mean between WTI crude oil futures market and Chinese stock index futures market or US stock index futures market. The relationship in mean between WTI crude oil futures prices and S&P 500 stock index futures, or CSI 300 stock index futures is we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…There are many studies explaining the lead & lag relationship of spot and future prices of crude oil like in (Bekiros & Diks, 2008) shows the bidirectional causal linkage of WTI crude oil and (Wang & Wu, 2013) also found that the long term relationship exists between futures and spot prices of WTI Crude Oil but in regime only and the price differentials are greater than the threshold value. Looking at the relationship of futures prices of crude oil and stock index futures, we found that in (Lu et al, 2021) stock index futures of US shows causality with WTI Crude oil futures having weak significance as compared to china. Also, the short term fluctuations of WTI futures have less influence on Chinese index futures than US.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…There are many studies explaining the lead & lag relationship of spot and future prices of crude oil like in (Bekiros & Diks, 2008) shows the bidirectional causal linkage of WTI crude oil and (Wang & Wu, 2013) also found that the long term relationship exists between futures and spot prices of WTI Crude Oil but in regime only and the price differentials are greater than the threshold value. Looking at the relationship of futures prices of crude oil and stock index futures, we found that in (Lu et al, 2021) stock index futures of US shows causality with WTI Crude oil futures having weak significance as compared to china. Also, the short term fluctuations of WTI futures have less influence on Chinese index futures than US.…”
Section: Introductionmentioning
confidence: 87%
“…Crude oil futures are the derivative instruments which not only help the market participants to manage risk but are also considered as a part of investment portfolios by financial market participants. Some of the studies like (Lu et al, 2021; see also LI et al,2021) evidenced that in the Chinese derivative market, crude oil futures are good hedging tools.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Figuerola-Ferretti et al (2020) associate the 2014 supply shock with OPEC’s announcement in November 2014. This has been recently addressed by Lu et al (2021) as a structural break when modeling the relationship between WTI crude oil and Chinese stock index futures.…”
Section: Lead Lag Relationship Before and After The Gfc And After The...mentioning
confidence: 99%
“…Similarly, Ren et al [ 26 ] use the thermal optimal route approach to study the SSE 50 Index and its derivatives and find that the stock index leads the index future, while the index option leads the index future. Lu et al [ 27 ] investigate the link between WTI crude oil futures and S&P 500 index futures or CSI 300 futures and find that the mean link between them is diminishing.…”
Section: Introductionmentioning
confidence: 99%